IHC Expression Relationships MMP7 and VEGF With Normal Ovaries and Ovarian Pathologies - Rusda, Muhammad; Rivany, Riza; Hasibuan, Citra Lestari; Lutan, Delfi; Aldiansyah, Dudy; Adella, Cut Adeya (Sumatera Medical Journal, 2019)
To investigate the association of MMP7 and VEGF expression with ovarian cancer, benign ovarian cysts, and normal ovaries. This study was analytical research with case-control design. In the study, IHC expression of MMP7 and VEGF was carried out on paraffin block of ovarian cancer tissue, benign ovarian cyst, and normal ovary. In 40 subjects with ovarian tumors, 17 patients were found with positive MMP7 expression. In the control group, no subjects were found with positive MMP7 expression. There was a significant relationship between MMP7 expression and ovarian tumor incidence. Meanwhile, in 40 subjects with ovarian tumors, 21 patients were found with positive VEGF expression. In the control group, no subjects with positive VEGF expression were found. There was a significant relationship between VEGF expression and ovarian tumor incidence. There was a significant relationship between MMP7 and VEGF expression with ovarian tumor incidence.